2022
DOI: 10.3390/microorganisms10122398
|View full text |Cite
|
Sign up to set email alerts
|

Updates on Group B Streptococcus Infection in the Field of Obstetrics and Gynecology

Abstract: Group B Streptococcus (GBS, Streptococcus agalactiae) is a Gram-positive bacterium that is commonly found in the gastrointestinal and urogenital tracts. However, its colonization during pregnancy is an important cause of maternal and neonatal morbidity and mortality worldwide. Herein, we specifically looked at GBS in relation to the field of Obstetrics (OB) along with the field of Gynecology (GY). In this review, based on the clinical significance of GBS in the field of OBGY, topics of how GBS is being detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 134 publications
0
3
0
Order By: Relevance
“…With the widespread use of antibiotics, research focusing on the drug resistance to GBS and drug sensitivity test in vitro in recent years showed that GBS had a high drug resistance to erythromycin and clindamycin [ 11 ]. Antibacterial drugs with no or low drug resistance included cephalosporins, penicillin, vancomycin, and so on [ 12 ]. Given that vancomycin has certain hepatorenal toxicity to the body, it is not recommended as the first drug choice.…”
Section: Discussionmentioning
confidence: 99%
“…With the widespread use of antibiotics, research focusing on the drug resistance to GBS and drug sensitivity test in vitro in recent years showed that GBS had a high drug resistance to erythromycin and clindamycin [ 11 ]. Antibacterial drugs with no or low drug resistance included cephalosporins, penicillin, vancomycin, and so on [ 12 ]. Given that vancomycin has certain hepatorenal toxicity to the body, it is not recommended as the first drug choice.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial vaginosis is a mixed infection caused by an imbalance in normal vaginal flora, where lactobacillus is reduced and other bacteria multiply, mostly anaerobic bacteria ( Kamga et al, 2019 ). Bacterial vaginosis and aerobic vaginitis are considered to be associated with various severe obstetric complications, such as preterm birth, miscarriage, premature rupture of membranes, fetal infection, and low birth weight infants ( Choi et al, 2022 ). Abnormal vaginal flora can lead to cervical shortening, resulting in preterm birth.…”
Section: Gbs Related Clinical Diseases In Obstetrics and Gynecologymentioning
confidence: 99%
“…GBS is an anaerobic gram-positive, hemolytic coccus, which is mainly present in the lower part of the reproductive tract and digestive tract of women, threatening the life and health of pregnant women and newborns (1). Most women have GBS in the vagina, but GBS is not pathogenic to healthy women.…”
Section: Introductionmentioning
confidence: 99%